"We are not 100% free": narratives of continuity and change amongst women on the margins of post-apartheid South Africa - Mogstad, Heidi (Department of Political Studies, 2017)
A wide range of auto/biographies and life stories has narrated South Africa's transition from apartheid to non-racial liberal democracy. However, the vast majority of these works has viewed the transformation process through the eyes of men and women who have lived extraordinary and spectacular lives. Following Ndebele's (1994) recognition of the radical potential of attending to the lives of ordinary South Africans, this thesis shifts the focus from the extraordinary and spectacular to the ordinary and examines the personal life stories of two female rural-to-urban migrants who have lived their entire lives on the margins of society. Viewing 'the margins' and 'the ordinary' as powerful sites for the production of counterhegemonic discourses (ibid; hooks, 1990:145) the thesis also reflects on what the women's life stories can teach us about South Africa's transformation process and post-apartheid freedom twenty-two years on. The thesis documents a halting and ambiguous transformation process and its impact on two black women who have spent their entire lives on the margins of the South African society. Particular light is shed on the limited and uneven impacts of the post-apartheid state's historical remedies and attempts to make a clean break with the past. Tracing how women's agency has played out over nearly four decades, the thesis shows how apartheids' racial, gendered and spatial legacies endure and are reinforced by current neoliberal policies and urban planning. The women's narratives also illustrate a yawning gap between South Africa's ideological and constitutional commitments and the lived realities for women left out of the "liberal promise" of development and prosperity (Comaroff and Comaroff, 2001) By shifting the focus from the spectacular and extraordinary to the ordinary, the thesis ultimately challenges us to rethink the notion of 1994 as a watershed moment in the lives of women of colour. On the one hand, the women's narratives clearly demonstrate the women's great resilience and ability to fend for themselves and their families in the face of adversity. On the other, their narratives also show the importance of confronting one-dimensional images of black women as strong and enduring 'superwomen' with little need for social support and assistance. The thesis concludes by reflecting on the women's ambivalent experiences of post-apartheid freedom. By attending to the women's daily concerns and grievances, the thesis highlights the limits of liberal freedom and democracy in the context of on-going violence, precarity and material lack.